Pengaruh Budaya Organisasi Dan Kompensasi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Pt Wilmar Nabati Teluk Bayur Padang - ., Fadli; Sari, Marta Widian; Karlinda, Ai Elis (CV. ITTC INDONESIA, 2026)
This study aims to determine the influence of organizational culture and compensation on employee performance, with job satisfaction as an intervening variable at PT Wilmar Nabati Teluk Bayur Padang. This research employs a quantitative method with a causal approach. The population consists of all 80 employees of PT Wilmar Nabati Teluk Bayur Padang. Due to the relatively small population size, saturated sampling (census) was used, making the entire population the research sample. Data collection was conducted via questionnaires using a Likert scale. Data analysis was performed using Structural Equation Modelling (SEM) based on Partial Least Square (PLS) with SmartPLS 3.0 software. The results indicate significant findings: (1) Organizational culture has a positive and significant effect on job satisfaction; (2) Compensation has a positive and significant effect on job satisfaction; (3) Organizational culture has a positive but insignificant direct effect on employee performance; (4) Compensation has a positive but insignificant direct effect on employee performance; (5) Job satisfaction has a positive and significant effect on employee performance; (6) Organizational culture has a positive and significant effect on employee performance through job satisfaction; and (7) Compensation has a positive and significant effect on employee performance through job satisfaction. These findings confirm that a strong organizational culture and fair compensation are effective in improving employee performance primarily when they first create job satisfaction ..